Determinants of Output Growth Volatility in Nigeria - Okeowo, Adeniyi; Japinye, Oluwaseun Abayomi (Yayasan Sinergi Kawula Muda, 2025)
The paper analysed the impact of agricultural output, investment, population growth and industry growth on output growth volatility. Many researchers have considered the determinants of output growth volatility but the impact of the above-mentioned variables on output growth volatility is scanty in literature. The data were tested for unit roots using Augmented Dickey-Fuller (ADF). Autoregressive Distributed Model (ARDL) was used in the methodology. The short-run dynamic model shows that the above-mentioned variables must undergo substantial structural changes to exert a significant and stabilising effect on output growth volatility in Nigeria. With F statistics of 15.9 and the upper and lower bound of 4.8 and 2.0 respectively, the bounds test result shows that the variables are co-integrated. The paper recommends an export promotion industrial strategy that is accompanied by an import substitution strategy, the re-introduction of a Marketing Board, alongside the construction of irrigation canals in strategically designated agricultural zones, could play a pivotal role in reversing the trend of business and economic instability, thereby helping to curb the persistent volatility in output growth.